The accidental flatness constraint does not mean a wrong classical limit. (6th June 2022) - Engle, Jonathan; Rovelli, Carlo
Abstract: We shed some light on the reason why the accidental flatness constraint appears in certain limits of the amplitudes of covariant loop quantum gravity. We show why this constraint is harmless, by displaying how analogous accidental constraints appear in transition amplitudes of simple systems, when certain limits are considered.